Schizophrenia and suicide: systematic review of risk factors. - Hawton, K; Sutton, L; Haw, C; Sinclair, J; Deeks, J (2005)
BACKGROUND: Suicide risk is greatly increased in schizophrenia. Detection of those at risk is clinically important. AIMS: To identify risk factors for suicide in schizophrenia. METHOD: The international literature on case-control and cohort studies of patients with schizophrenia or related conditions in which suicide was reported as an outcome was systematically reviewed. Studies were identified through searching electronic databases and reference lists, and by consulting experts. RESULTS: Twenty-nine eligible studies were identified. Factors with robust evidence of increased risk of suicide were previous depressive disorders (OR=3.03, 95% CI 2.06-4.46), previous suicide attempts (OR=4.09, 95% CI 2.79-6.01), drug misuse (OR=3.21, 95% CI 1.99-5.17), agitation or motor restlessness (OR=2.61, 95% CI 1.54-4.41), fear of mental disintegration (OR=12.1, 95% CI 1.89-81.3), poor adherence to treatment (OR=3.75, 95% CI 2.20-6.37) and recent loss (OR=4.03, 95% CI 1.37-11.8). Reduced risk was associated with hallucinations (OR=0.50, 95% CI 0.35-0.71). CONCLUSIONS: Prevention of suicide in schizophrenia is likely to result from treatment of affective symptoms, improving adherence to treatment, and maintaining special vigilance in patients with risk factors, especially after losses.